The mediating effect of belongingness on the relationship between perceived stress and clinical learning environment and supervision among nursing internship students - Sameer A. Alkubati; Talal Al-Qalah; Basma Salameh; Ahmed Loutfy; Wesam T. Almagharbeh; Eddieson Pasay-an; Abdelaziz Hendy; Mohamed A. Zoromba; Heba E. El-Gazar; Maysa Abdalla Elbiaa; Shimmaa M. Elsayed (BMC Nursing)
Abstract Background Belongingness is considered an important factor contributing to a clinical learning environment for good learning outcomes and higher levels of satisfaction among nursing students. This study investigated the mediating influence of a sense of belonging on the relationship between the clinical learning environment and perceived stress. Methods This cross-sectional study was conducted using a convenience sample of 455 internship nursing students from August to November 2023. Data were collected using the Belongingness Scale-Clinical Placement Experience, Perceived Stress Scale, Clinical Learning Environment Scale, and Supervision Scale. Results The mean of nursing internship students’ belongingness was 121.27 ± 14.95. The majority of participants had moderate stress levels (83.3%). The direct effects analysis revealed a significant negative correlation between the clinical learning environment, supervision, and perceived stress (β = − 0.484, p < .001). Clinical learning environment and supervision had a positive direct effect on belongingness (β = 0.499, p < .001). Belongingness had a negative effect on perceived stress (β = − 0.163, p = .003). According to further indirect effect analysis (β = − 0.081, p = .003), the association between the clinical learning environment and supervision-perceived stress was mediated by belongingness. Overall, the results showed that felt stress was considerably affected by the clinical learning setting and supervision (β = − 0.565, p < .001). Conclusion A sense of belonging is a critical factor for alleviating the impact of an overwhelming environment. These findings emphasize the need to provide a positive environment that promotes the health of internship nursing students. Clinical trial number Not applicable.